2021
DOI: 10.1038/s41393-021-00717-2
|View full text |Cite
|
Sign up to set email alerts
|

Fecal diversion does not support healing of anus-near pressure ulcers in patients with spinal cord injury—results of a retrospective cohort study

Abstract: Study Design Retrospective cohort study including spinal cord injured patients with anus-near pressure ulcers. Objective The primary objective was to evaluate the impact of stool diversion via stoma on the decubital wound healing. Secondary objectives included the risk of complications and ulcer recurrence. Associations between the wound healing and potentially interfering parameters were determined. Setting Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…However, the evidence regarding the relationship between fecal contamination in patients with extensive PIs and the necessity for stoma placement remains inconclusive. Some studies, such as the 2021 retrospective cohort study ( Pussin et al, 2021 ), suggest that colostomies might not always be the optimal solution; the authors reported that stoma patients required more time (an average of 77 days) to achieve complete healing of anus-near PIs compared to non-stoma patients (59 days). Given the physical and psychological challenges associated with stoma formation, the study's authors concluded that a colostomy might not be the standard solution for all patients with PIs near the anus.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence regarding the relationship between fecal contamination in patients with extensive PIs and the necessity for stoma placement remains inconclusive. Some studies, such as the 2021 retrospective cohort study ( Pussin et al, 2021 ), suggest that colostomies might not always be the optimal solution; the authors reported that stoma patients required more time (an average of 77 days) to achieve complete healing of anus-near PIs compared to non-stoma patients (59 days). Given the physical and psychological challenges associated with stoma formation, the study's authors concluded that a colostomy might not be the standard solution for all patients with PIs near the anus.…”
Section: Discussionmentioning
confidence: 99%
“…The working group concluded that, where appropriate, patients with pelvic PIs should undergo fecal diversion to reduce risk of downstream fecal contamination of the surgical site 91 . Surgical intervention should consider debridement of any necrotic bone or large bony prominences.…”
Section: Surgical Algorithmmentioning
confidence: 99%
“…The working group concluded that, where appropriate, patients with pelvic PIs should undergo fecal diversion to reduce risk of downstream fecal contamination of the surgical site. 91 Surgical intervention should consider debridement of any necrotic bone or large bony prominences. In addition, multiple bone biopsies, harvested during debridement, should be sent to pathology to evaluate for osteomyelitis and to microbiology to identify bacterial pathogens for targeted antibiotic therapy.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Para el manejo de deposiciones existen estudios controversiales sobre la utilidad de colostomía (44) . Nuestro grupo recomienda utilizar el protocolo diseñado en conjunto con el equipo de Nutrición, el cual consiste en lograr deposiciones blandas para facilitar la higiene y en el caso de que la lesión sea < 6 cms desde el ano, se sugiere evaluar la derivación fecal (45) . 5.…”
Section: Coberturaunclassified